Investigation of bulk acoustic microwaves excited by an interdigital transducer - Reshotka, O. G.; Hayduchok, V. G.; Vakiv, N. M. (Technology and design in electronic equipment, 2015)
Excitation of bulk and surface acoustic waves with the interdigital transducer (IDT), which is deposited on the surface of a piezoelectric crystal, is widely used in the development of devices in acoustoelectronics and in the design of the microwave acousto-optic deflectors. Excitation of bulk acoustic waves by IDT in the devices on surface acoustic waves leads to the appearance of spurious signals. At the same time, excitation of bulk acoustic waves with IDT from the surface of lithium niobate crystals allows creating high frequency acousto-optic deflectors, which makes possible to significantly simplify the technology of their production. Therefore, significant attention is paid to the task of excitation and distribution of bulk acoustic waves with IDT, including recent times by the method of simulation of their excitation and distribution. The obtained theoretical results require experimental verification. This paper documents the visualization of acoustic beams excited with IDT from the XY-surface of lithium niobate crystals. The Bragg cells with LiNbO3 crystals coated with IDT with a different period of electrodes were manufactured for the experimental research of excitation and distribution of bulk acoustic waves. Visualization results have shown that the acoustic waves excited with IDT distribute in both the Fresnel zone and the Fraunhofer zone. The length of these zones is caused by individual elementary emitters, of which consists the IDT (by their size). At the same time, the far zone for IDT is located at distances much greater than the actual size of the LiNbO3 crystals. This peculiarity is not always taken into account when calculating diffraction. The achieved results can be used to design high-frequency acousto-optic devices, as well as in the development of devices based on surface acoustic waves.